The impact of various post-exercise interventions on the relief of delayed-onset muscle soreness: a randomized controlled trial - Wei, Ming; Liu, Xin; Wang, Siyu (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to compare the effectiveness of various recovery interventions in alleviating delayed-onset muscle soreness (DOMS), focusing on the comparative effects of vibration therapy, functional electrical stimulation (FES), static stretching, massage therapy, and cold-water immersion (CWI).MethodsThis randomized controlled trial (RCT) was conducted at the university’s physical training center from September 2024 to October. A total of 30 healthy male university students were recruited and randomly assigned to six groups, with five participants in each group. Healthy students were recruited via public announcements and randomly assigned to 6 groups: massage therapy (Group A), CMI (Group B), vibration therapy (Group C), static stretching (Group D), FES (Group E), and control (Group F). After DOMS was induced in the quadriceps, participants received the designated recovery interventions. Assessments were conducted at baseline, immediately post-exercise, and at 24, 48, and 72 h, including tensiomyography (TMG), pressure pain threshold (PPT), knee joint range of motion (ROM), isokinetic strength (ISOK), and biochemical markers (CK, Ca2+, IL-6).ResultsThirty participants completed the study. Group C demonstrated the greatest improvement in contraction time (Tc) at 72 h (p < 0.05) and the most significant reduction in IL-6 levels (p < 0.01). Group E significantly enhanced peak concentric power recovery from 24 to 72 h (p < 0.001) and ranked second to Group B in early-phase IL-6 regulation (p < 0.05). Group D demonstrated a significant main effect on ROM recovery (F = 3.41, p < 0.05), while Group A most effectively reduced CK levels and stabilized Ca2+ homeostasis (p < 0.05). All variables showed significant main effects of time (Tc: η2 = 0.760; Dm: η2 = 0.824; IL-6: η2 = 0.854), with interaction effects noted for Dm (η2 = 0.360) and peak concentric power (η2 = 0.336).ConclusionVibration therapy effectively enhanced muscle responsiveness by reducing Tc. Massage therapy was most effective in reducing IL-6, CK, and Ca2+ levels, alleviating muscle stiffness and soreness, and facilitating tissue repair. FES significantly increased PPT and muscle strength, mitigating DOMS-related pain and functional decline. Static stretching offered notable benefits in enhancing joint ROM, whereas CMI effectively suppressed early inflammatory responses.